Optimization and biological evaluation of thiazole-bis-amide inverse agonists of RORγt. Issue 12 (15th June 2020) - Gege, Christian; Albers, Michael; Kinzel, Olaf; Kleymann, Gerald; Schlüter, Thomas; Steeneck, Christoph; Hoffmann, Thomas; Xue, Xiaohua; Cummings, Maxwell D.; Spurlino, John; Milligan, Cynthia; Fourie, Anne M.; et al.
Graphical abstract: Abstract: The nuclear receptor retinoic acid receptor-related orphan receptor gamma t (RORγt) is a transcription factor that drives Th17 cell differentiation and IL-17 production in both innate and adaptive immune cells. The IL-23/IL-17 pathway is implicated in major autoimmune and inflammatory diseases. RORγt lies at the core of this pathway and represents an attractive opportunity for intervention with small molecule therapeutics. Despite diverse chemical series having been reported, combining high potency and nuclear receptor selectivity with good physicochemical properties remains a challenging endeavor in the field of RORγt drug discovery. We recently described the discovery and evaluation of a new class of potent and selective RORγt inverse agonists based on a thiazole scaffold. Herein we describe the successful optimization of this class by incorporation of an additional amide moiety at the 4-position of the thiazole core. In several optimization cycles, we have reduced human PXR activation, improved solubility, and increased potency while maintaining nuclear receptor selectivity. X-ray crystallographic analysis of compound 1g bound in the sterol binding site of the ligand binding domain of RORγt was largely consistent with an earlier structure, guiding further insight into the molecular mechanism for RORγt inhibition with this series. Compound 1g is orally bioavailable, potent in a human whole blood assay and proved to be efficacious in an ex-vivo IL-17A assay, and was selected for preclinical evaluation.